The contextualization of decision-making processes in the Limpopo provincial government tender board - Makhura, Mochiphisi Piet (My University, 2005)
Refer to document
Thesis (MPA.) --University of Limpopo, 2005
Keywords: Tender process; Awarding of tenders; Limpopo Provincial Government; Public contracts -- South Africa; Limpopo (South Africa) - Procurement.